Formulation and Physical Stability Evaluation of Sacha Inchi (Plukenetia volubilis L.) Oil-Based Body Lotion as Skin Moisturizer - Neni Sri Gunarti; Richa Putri Immelia; Farhamzah; Eko Sriwahyuningsih (Indonesian Journal of Health Research and Development, 2025)
Background: Sacha Inchi oil (Plukenetia volubilis L.) is rich in essential fatty acids and antioxidants, making it a promising active ingredient in body lotion formulations for skin moisturization and protection.Aims and Scope: This study aimed to evaluate the effect of varying concentrations of Sacha Inchi oil on the physical stability, moisturizing effectiveness, and user acceptability of body lotion formulations.Methods: Three body lotion formulas were prepared with Sacha Inchi oil at concentrations of 5% (F1), 6% (F2), and 7% (F3). Evaluations included organoleptic observations, pH measurement, viscosity, spreadability, moisturizing effectiveness using a skin analyzer, irritation tests, and hedonic tests involving 20 panelists.Result: Formula F3 demonstrated the best moisturizing effectiveness, increasing skin moisture by 20.45%, with a pH of 6.45, viscosity of 6,150 cP, and spreadability of 5.4 cm. Although F3 had the highest moisturizing effect, F2 was the most preferred by panelists, with 83.3% indicating strong preference for texture and 72.2% for spreadability. All formulas showed no signs of irritation.Conclusion: The body lotion containing 7% Sacha Inchi oil (F3) was the most effective in enhancing skin moisture, while the 6% formulation (F2) was the most favorable in terms of sensory attributes.